2013
DOI: 10.1038/srep02389
|View full text |Cite
|
Sign up to set email alerts
|

Arginine insertion and loss of N-linked glycosylation site in HIV-1 envelope V3 region confer CXCR4-tropism

Abstract: The third variable region (V3) of HIV-1 envelope glycoprotein gp120 plays a key role in determination of viral coreceptor usage (tropism). However, which combinations of mutations in V3 confer a tropism shift is still unclear. A unique pattern of mutations in antiretroviral therapy-naive HIV-1 patient was observed associated with the HIV-1 tropism shift CCR5 to CXCR4. The insertion of arginine at position 11 and the loss of the N-linked glycosylation site were indispensable for acquiring pure CXCR4-tropism, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
5
19
1
Order By: Relevance
“…The lower indel rates might also be attributed in part to compensatory mutations to preserve structural interactions in V3 [28]. For example, an arginine insertion at position 11 of V3 confers CXCR4 tropism tends to be accompanied by a single amino acid deletion near the C-terminal of V3 [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower indel rates might also be attributed in part to compensatory mutations to preserve structural interactions in V3 [28]. For example, an arginine insertion at position 11 of V3 confers CXCR4 tropism tends to be accompanied by a single amino acid deletion near the C-terminal of V3 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of comparative studies have examined indel rates in the HIV-1 env gene encoding gp120 and gp41. Wood et al [40], for one, found that indels preferentially accumulate in the variable loops of gp120 compared to the remainder of this sequence, while other studies have suggested that variable loop indels correspond with HIV-1 transmission and modulate coreceptor switching [9, 36].…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 Env-mediated Cell-Cell Fusion Assay-The HIV-1 Env-mediated cell-cell fusion assay was performed as described previously (25,26) with minor modifications. To prepare the effector cells, the envelope expression vector (1 g of plasmid of pCXN/Env JRFL , pCXN/Env NL4-3 , or pVSV-G) and HIV-1 "Trans-activator of Transcription" (Tat) expression vector (1 g of plasmid of pCDNA6.2/HIV-tat) were transfected into HEK293 cells (5 ϫ 10 5 cells) using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of N‐linked glycosylation characteristic referred to CCR5 usage. It previously reported that loss of N‐linked glycosylation site supported for a switch in the coreceptor used and conferred to CXCR4 usage . The loss of N‐linked glycosylation site might lead to change the orientation of V3 loop and alter gp120 interaction surface for coreceptor binding and influence coreceptor usage.…”
Section: Discussionmentioning
confidence: 99%
“…It previously reported that loss of N-linked glycosylation site supported for a switch in the coreceptor used and conferred to CXCR4 usage. [33][34] and reported the concordance rates ranging from 79% to 97%. [35][36][37][38][39] Many studies determined the prevalence of HIV-1 coreceptor usage in HIV-1 infected children; they have shown that either R5 or X4 viruses can be highly observed using proviral DNA or plasma RNA.…”
Section: Prevalence Of Hiv-1 Coreceptor Usage Based On Age Year Ofmentioning
confidence: 99%